2011
DOI: 10.1002/app.34045
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal and nonisothermal crystallization kinetics of poly(ϵ‐caprolactone)

Abstract: With increasing environmental awareness, evaluating the potential of biopolymers as a substitute for traditional materials has been of great interest. Crystallization kinetics provides fundamental knowledge required for evaluation, playing vital role in determining the final properties of the product. In this study, the isothermal and nonisothermal crystallization kinetics of poly(e-caprolactone) (PCL) were investigated with the help of various models. The Avrami model best described the isothermal crystalliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…Moreover, for SCL# copolymers, n values were similar to those obtained for linear PCL, with calculated values between 2.4 and 3.4 (see Table 2). It is important to highlight that these values refer to a three-dimensional heterogeneous nucleation and they are in good agreement with values already reported [33,36,56]. On the other hand, HEMACL# copolymers show values of n exponent from 1.8 to 2.6, Table 1: Chemical and thermal characterization of synthesized linear PCL and PDMS-OH homopolymers, and PCL-based copolymers.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Moreover, for SCL# copolymers, n values were similar to those obtained for linear PCL, with calculated values between 2.4 and 3.4 (see Table 2). It is important to highlight that these values refer to a three-dimensional heterogeneous nucleation and they are in good agreement with values already reported [33,36,56]. On the other hand, HEMACL# copolymers show values of n exponent from 1.8 to 2.6, Table 1: Chemical and thermal characterization of synthesized linear PCL and PDMS-OH homopolymers, and PCL-based copolymers.…”
Section: Resultssupporting
confidence: 87%
“…In this sense, the understanding of the crystallization behavior of branched and linear copolymers based on PCL at temperatures lower than that corresponding to the linear homopolymer could lead to changes in processing parameters, especially if they are targeted for specific purposes. In such a sense, the thermal stabilities of the studied polymers were analyzed, and Avrami's isothermal crystallization model was employed to calculate kinetic parameters from the crystallization process [32][33][34][35][36]. It is inferred that data obtained from this analysis will provide useful information for further applications, particularly if these materials or combinations of them are planned for using as potential inks in 3D-printing or electrospinning devices [5][6][7]16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is concluded that the Ozawa model is not appropriate to provide an adequate description of non-isothermal crystallization kinetics of PA56. Similar results have been reported that the plots deviate from a good linearity with the Ozawa model [27,28]. The reason for that failure may be the inaccurate assumption of a constant cooling over the entire crystallization process.…”
Section: Non-isothermal Crystallization Based On Ozawa Modelsupporting
confidence: 84%